Magical Realism and Marvelous Real: Interpretative Models for the Latin America Cultural History - Álvarez Pitaluga, Antonio (2020)
The article proposes a historical approach to literary categories, magical realism and Marvelous Real. Their potentialities are analyzed as interpretive models for the cultural history of Latin America. It is intended to demonstrate that its most recognized representatives, Miguel Ángel Asturias and Alejo Carpentier, structured these contributions from a historicist perspective as trans-disciplinary models for the cultural compression of Latin America.